Some features of the architecture of St. Basil's Cathedral - Semenov I. V. (Fall School Marathon, 2019)
The work presents a number of features of a remarkable architectural monument - St. Basil's Cathedral. The author of the article gives a description of the temple given by Academician D.S. Likhachev, and his own impressions of visiting the Cathedral.
Keywords: Собор Василия Блаженного; Basil's Cathedral; a historical and architectural monument; историко-архитектурный памятник; характеристика Собора Василия Блаженного